2021
DOI: 10.3390/designs5040078
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neural Network Models for the Prediction of the Aggregate Base Course Compaction Parameters

Abstract: Laboratory tests for the estimation of the compaction parameters, namely the maximum dry density (MDD) and optimum moisture content (OMC) are time-consuming and costly. Thus, this paper employs the artificial neural network technique for the prediction of the OMC and MDD for the aggregate base course from relatively easier index properties tests. The grain size distribution, plastic limit, and liquid limits are used as the inputs for the development of the ANNs. In this study, multiple ANNs (240 ANNs) are test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Khuntia et al [12] used Artificial Neural Network (ANN), Least Squares Support Vector Machine (LS-SVM), and Multiple Adaptive Regression Spline Curve (MARS) to develop a prediction model for the compaction parameters of sandy soils, and the MARS model was more accurate. Othman [26] constructed a prediction model for aggregate base materials by ANN trained with different numbers of hidden layers, different numbers of hidden layer neurons, and three activation functions. The results showed that the hyperbolic tangent function (Tanh) is the most effective activation function and the performance of the ANN deteriorates with an increase in the number of hidden layers or the number of neurons per hidden layer.…”
Section: Introductionmentioning
confidence: 99%
“…Khuntia et al [12] used Artificial Neural Network (ANN), Least Squares Support Vector Machine (LS-SVM), and Multiple Adaptive Regression Spline Curve (MARS) to develop a prediction model for the compaction parameters of sandy soils, and the MARS model was more accurate. Othman [26] constructed a prediction model for aggregate base materials by ANN trained with different numbers of hidden layers, different numbers of hidden layer neurons, and three activation functions. The results showed that the hyperbolic tangent function (Tanh) is the most effective activation function and the performance of the ANN deteriorates with an increase in the number of hidden layers or the number of neurons per hidden layer.…”
Section: Introductionmentioning
confidence: 99%